O cinema como prática educativa no ensino médio: Projeto O Cinema vai à escola - Moura, Marcilene Rosa Leandro (2013)
Considering the changes in Brazilian education, consolidated from educational reforms promoted by the Federal Government in mid of 1990, attending the determinations made explicit in the documents produced by the World Conference on Education for All and the Report to UNESCO of the International Commission on Education for the Twenty-first Century (Delors Report) that propose to achieve an education that meets the demands of the contemporary world through the pedagogy of learning to learn also known as Pedagogical Competence, the writing in question discusses how these issues are spread in the project The Cinema Goes to School - the use of cinematographic language in education that integrate series of actions proposed by the Sao Paulo State Board of Education from the implementation of State Official Curriculum in 2008. The Educational Project referred, aimed at secondary school students from public schools, search in synthesis, promote by displaying several cinematographic productions the development of competences and skills, particularly the reader and the writer, from the perspective of providing an education that promotes the resources cognitive mobilization necessary knowledge to attend social demands, aiming the changes in the contemporary world. The research was made in several stages and involved the review of existing bibliography, application of questionnaires and semi-structured interviews with the pedagogical coordinators teachers and high school teachers from public schools located in the city of Sorocaba / SP. Moreover, it was made the tab data of on-line research made by SEE / SP on the application of the educational project in schools. Although teachers have the concern to meet the curriculum proposed by the SEE / SP particularly through the contents contained in the Book of the Teacher / Student, does it almost innocent, considering his lack of knowledge about the current educational policy both national and state even considering indispensable the content fulfillment presented in educational materials provided by SEE / SP aiming to be fundamental to provides the students with knowledge that will enable their entry into the labor market as well as in higher education.